2004
DOI: 10.1254/jphs.94.81
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effects of Aqueous Extract of Magnolia officinalis on Human Mesangial Cell Proliferation by Regulation of Platelet-Derived Growth Factor-BB and Transforming Growth Factor-β1 Expression

Abstract: Abstract. Mesangial cell (MC) proliferation, mediated by platelet-derived growth factor (PDGF)-BB, transforming growth factor (TGF)-b1, and cyclin-dependent kinases (CDK), is the common feature of glomerulosclerosis. Magnolia officinalis, stem bark of Machilus thunbergii S., has multiple pharmacological effects. In this study, we investigated the influence of aqueous extract of Magnolia officinalis on MC proliferation, DNA synthesis, and expression of PDGF-BB, TGF-b1, CDK1, CDK2, and CDK4 in fetal bovine serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Additionally, other studies showed that honokiol inhibited angiogenesis by interfering with VEGFR2 autophosphorylation [14] and subsequently blocking the VEGF-induced Rac activation [28], which is required for endothelial cell migration and proliferation [29]. In addition, regulation of platelet-derived endothelial cell growth factor and TGF-b expression [30], inhibition of nitric oxide synthesis and TNF-a [31] might be involved in this event. Further studies will be conducted to elucidate the intensive mechanism of honokiol in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other studies showed that honokiol inhibited angiogenesis by interfering with VEGFR2 autophosphorylation [14] and subsequently blocking the VEGF-induced Rac activation [28], which is required for endothelial cell migration and proliferation [29]. In addition, regulation of platelet-derived endothelial cell growth factor and TGF-b expression [30], inhibition of nitric oxide synthesis and TNF-a [31] might be involved in this event. Further studies will be conducted to elucidate the intensive mechanism of honokiol in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits nitric oxide synthesis and TNF-a expression. 108,109 In animal experiments, it suppresses the proliferation of blood vessel endothelial cells more than other types of cells and thereby reduces tumor growth. 110,111 Silybum marianum (Milk Thistle) Silibinin and silymarin are polyphenolic flavonoids isolated from the fruits or seeds of S. marianum (L.) Gaertn.…”
Section: Magnolia Officinalis (Chinese Magnolia Tree)mentioning
confidence: 99%
“…It also inhibits nitric oxide synthesis and TNF-a expression. 108,109 In animal experiments, it suppresses the proliferation of blood vessel endothelial cells more than other types of cells and thereby reduces tumor growth.…”
Section: Magnolia Officinalis (Chinese Magnolia Tree)mentioning
confidence: 99%
“…Nitrik oksit sentez ve tümör nekroz faktör alfa (TNF-a) ekspresyonunu da azaltmaktadır. [31,32] Silybum marianum (Milk thistle)…”
Section: Curcuma Longa (Kurkumin)unclassified